Kitab Fara’id al-Qur’an - Arivaie Rahman; Sri Erdawati (SUHUF, 2020)
Abstract: This article discusses the book of Fara’id Al-Qur’an in the book Jam'u Jawami' al-Musannafat, a work of interpretation in Malay from Aceh. This research confirms that there was the stagnation in the production of the Malay Quranic exegesis texts in the early period. Although the manuscript contains a few pages only, the presence of the Fara’id Al-Qur’an has succeeded in generating the productivity of the Qur’anic exegesis at the end of the 17th to the 19th centuries. The text was positioned more as the text of inheritance jurisprudence (fiqh waris) than that of the Qur’anic exegesis independently. The author is anonymous, but to be certain was a scholar whose position was very important in the Sultanate of Aceh. The Reference of Fara’id Al-Qur’an exegesis cannot be determined and has a difference with the text of Tarjuman al-Mustafid and al-Jalalain. This study corrects the mistakes of the previous research stating that the Fara’id Al-Qur’an only interpreted Surah an-Nisa'/4: 11-12, whereas the interpretation of the 176 verse is also included in the book.